COMPARISON OF CURRENT LEVEL CYCLEWAYS IN OSTRAVA AND FINLAND (Perner's Contacts, 2011)
The paper deals current level cycleways in Finland and Ostrava. The specificexamples show the state of cycleways and the opportunity to solve some of thepromlem's place on finnish cycleways. Further shows tThe paper deals current level cycleways in Finland and Ostrava. The specific examples show the state of cycleways and the opportunity to solve some of the promlem's place on finnish cycleways. Further shows to some dangerous places on Ostrava's cycleways.o some dangerous placeson Ostrava's cycleways.The paper deals current level cycleways in Finland and Ostrava. The specific examples show the state of cycleways and the opportunity to solve some of the promlem's place on finnish cycleways. Further shows to some dangerous places on Ostrava's cycleways.
Keywords: cycleway; safety of cyclists; green transport